Política fiscal no Brasil, 1994-2008 - Santos, Marcelo [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
O trabalho apresenta um estudo (panorama) da política fiscal no Brasil no período de 1994 a 2008, analisando as receitas federais, as despesas da União, as variáveis Resultado Primário do Governo Central, Necessidade de Financiamento do Setor Público (NFSP) e Dívida Líquida do Setor Público (DLSP). Afirmamos que a política fiscal no Brasil foi conduzida de acordo com o novo regime macroeconômico e que as medidas adotadas no âmbito da política fiscal resultaram na construção de um novo regime fiscal. Coube à política fiscal, nesse novo regime, o papel de sustentabilidade da dívida, por meio de políticas adequadas de gastos e receitas, conduzida de maneira que pudessem ser alcançadas as metas de resultado primário

The paper presents a study of fiscal policy in Brazil from 1994 to 2008, analyzing the federal revenues, the expenditures of the whole government sector in Brazil, the Primary Result of the Central Government, the of the Public Sector Borrowing Requirements (PSBR) and Public Sector Net Debt . We assert that fiscal policy in Brazil was conducted in accordance with the new macroeconomic regime, and that the measures adopted in that framework of fiscal policy resulted in the construction of a new fiscal regime. The fiscal policy in this new system has the role of debt sustainability, with suitable revenue and spending policy, conducted in a manner that could achieve the goals of the primary results
Keywords: Economia; Política tributária; Divida publica; Indicadores fiscais; Receitas e despesas federais; Novo regime fiscal; Fiscal policy; Federal revenue and spending; Fiscal and public debt; New fiscal regime